Palmistichus elaeisis (Hymenoptera: Eulophidae) Parasitizing Pupae of the Passion Fruit Pest Agraulis vanillae vanillae (Lepidoptera: Nymphalidae) - Rodríguez-DImaté, Francisco Andrés; Poderoso, Júlio César Melo; Ribeiro, Rafael Coelho; Brügger, Bruno Pandelo; Wilcken, Carlos Frederico [UNESP]; Serrão, José Eduardo; Zanuncio, José Cola (De Gruyter, 2016)
Agraulis vanillae vanillae L. (Lepidoptera: Nymphalidae) is a pest of Passiflora species (Malpighiales: Passifloraceae). The parasitism of A. vanillae vanillae pupae by Palmistichus elaeisis Delvare & LaSalle (Hymenoptera: Eulophidae) was evaluated. Ten 72-h-old mated P. elaeisis females were confined for 48 h with each 24-h-old A. vanillae vanillae pupa. These exposed pupae were transferred to glass tubes until the emergence of the parasitoid adults. The percentages of parasitism and emergence, number that emerged, sex ratio, body size, width of the head capsule, and longevity of P. elaeisis females and males were similar to those of P. elaeisis reared with various other hosts. These results this indicated that it is practical to rear this parasitoid with A. vanillae vanillae pupae to provide the parasitoid for use in biological control programs.
Keywords: Biological control; Parasitism; Passiflora